2016
DOI: 10.1089/neu.2014.3847
|View full text |Cite
|
Sign up to set email alerts
|

Is Traumatic Brain Injury Associated with Reduced Inter-Hemispheric Functional Connectivity? A Study of Large-Scale Resting State Networks following Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) often has long-term debilitating sequelae in cognitive and behavioral domains. Understanding how TBI impacts functional integrity of brain networks that underlie these domains is key to guiding future approaches to TBI rehabilitation. In the current study, we investigated the differences in inter-hemispheric functional connectivity (FC) of resting state networks (RSNs) between chronic mild-to-severe TBI patients and normal comparisons (NC), focusing on two externally oriented netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 72 publications
5
38
0
Order By: Relevance
“…Indeed, one limitation of the study lies in the fact that different types of severity information were available for participants with TBI. The Mayo classification system (Malec et al, 2007), which allows researchers to indicate TBI severity by combining all available pieces of information, has been extensively used in a wide variety of studies (Baxter et al, 2013; Ham et al, 2014; Rigon, Duff, McAuley, Kramer, & Voss, 2015) since its publication. However, because in the current study determined severity by different factors for each participant, within group comparisons and correlations between TBI severity and behavioral performance were not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one limitation of the study lies in the fact that different types of severity information were available for participants with TBI. The Mayo classification system (Malec et al, 2007), which allows researchers to indicate TBI severity by combining all available pieces of information, has been extensively used in a wide variety of studies (Baxter et al, 2013; Ham et al, 2014; Rigon, Duff, McAuley, Kramer, & Voss, 2015) since its publication. However, because in the current study determined severity by different factors for each participant, within group comparisons and correlations between TBI severity and behavioral performance were not feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these measures were collected as part of battery administered to the University of Iowa TBI registry patients (Rigon, Duff, McAuley, Kramer, & Voss, 2016; Rigon, Turkstra, et al, 2016; Rigon, Turkstra, Mutlu, & Duff, In press; Rigon, Voss, et al, 2016). Due to study attrition, results for WAIS, CVLT, Trails, and BSI were missing from one participant in the HC group.…”
Section: Methodsmentioning
confidence: 99%
“…Structural connectivity following TBI has traditionally been examined using diffusion tensor imaging (DTI), which provides a way to assess integrity and directionality of white matter tracts traveling between nodes of a given brain network (Hulkower et al, 2013, Kennedy et al, 2009, Sharp and Ham, 2011). However, in the past decade several studies have employed resting state functional connectivity (rs-FC) measured with functional magnetic resonance imaging (fMRI) to investigate integrity of brain networks in TBI populations (Arenivas et al, 2014, Bonnelle et al, 2011, Marquez de la Plata et al, 2011, Palacios et al, 2013, Rigon et al, 2016a, Sharp et al, 2011). Rs-FC measures the correlation between fluctuations in the hemodynamic fMRI signal between regions throughout the brain that form large-scale brain networks (Biswal et al, 1995, Fox et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wealth of studies have found abnormalities in both white matter integrity (Hulkower et al, 2013, Sidaros et al, 2008) and patterns of rs-FC in several large-scale brain networks in TBI populations (Rigon et al, 2016a, Stevens et al, 2012), as well as correlations between these measures and behavioral performance (Bonnelle et al, 2011, Ham et al, 2014, Sours et al, 2014, Rigon et al, 2016c). However, only one study has explored the relationship between white matter integrity and facial-affect recognition ability in individuals with moderate-severe TBI: Genova and colleagues (Genova et al, 2015) found that performance on emotion recognition tasks was positively correlated with fractional anisotropy of the inferior fronto-occipital and inferior longitudinal fasciculus, which connect visual regions with temporal and prefrontal areas involved in affective processing and decision making.…”
Section: Introductionmentioning
confidence: 99%